The effectiveness of camalexin against botrytis cinerea / K P. Chong …[et al.] - Chong, K.P.; Mansfield, J.W.; Bennett, M.H.; Rossiter, J. F. (2006)
The antimicrobial activity and fungitoxicity of phytoalexin from Arobidopsis thaliana, camalexin against Botrytis cinerea had been studied in vitro. In a series of experiments, the activity of camalexin had been measured against spores and various types of germ tubes of B. cinerea. Activities were assessed based on the percentage of germination and mortality of germ tube besides germ tube development after challenged by camalexin. We found ungerminated conidia were more susceptible than older sporelings to the fungitoxic and inhibitory effects of camalexin. Higher concentrations of camalexin tested, produced significantly higher percentage of mortality and found to be more inhibitory compared to other lower concentrations tested for both conidia and germ tube.